ANALISIS TINGKAT KESEHATAN KSPPS USAHA BAROKAH JATIPURNO (Studi Kasus Syariah KPPS Usaha Barokah Jatipurno) - Hanik Fatona Ernawati; Agus Marimin; Hadi Samanto (ITB AAS INDONESIA Surakarta, 2025)
This study aims to analyze the health level of the Sharia Savings and Loan Cooperative (KSPPS) Usaha Barokah Jatipurno, which plays a vital role in supporting micro and small businesses based on sharia principles. The research uses a quantitative descriptive approach with financial ratio analysis, covering aspects of capital, asset quality, management, profitability, and liquidity. Data were collected through documentation studies of financial reports, structured interviews with cooperative management, and direct observation of cooperative operations. The analysis results show that KSPPS Usaha Barokah Jatipurno's Capital Adequacy Ratio (CAR) increased from 25% to 27% over two years, the problematic productive asset ratio remained stable at 3%, and the current ratio stood at 2.0, indicating good liquidity conditions. With a health assessment score of 84%, the cooperative is categorized as being in a